Human factors in provision of safe anaesthesia: A continuous effort - Mohd Hanafiah, Farah Nadia; Abd Halim, Nurhidayah (Malaysian Society of Anaesthesiologist, 2021)
Pursuing safe anaesthesia is a never-ending journey. Enormous progression had been made previously and this is still an ongoing process. The bulk of anaesthesia that used to be only performed in operating theatres have moved further beyond. Failure to provide a safe anaesthesia is catastrophic. Human factors played an important role, and this article will touch upon communication, teamwork, situational awareness, human error and the usage of checklists. During our current situation of COVID-19 pandemic, providing safe anaesthesia is not solely limited to patients but now it also involves the healthcare providers. Guidelines pertaining to COVID-19 management had been published for healthcare providers to follow. Ultimately, more studies and guidelines are required in our own setting in providing a safe anaesthesia